Socio-Culture and Health Factors Determining Stunting in Children Under-Five in Banggai Kepulauan Regency, Central Sulawesi - Yuniati, Eka; Triratnawati, Atik (Universitas Andalas, 2024)
Stunting is still a serious global health problem and needs to be addressed. Stunting is defined as a problem in the growth and development of children under the age of five (toddlers). The purpose of this study was to reveal the factors that cause stunting in toddlers. The research location chosen was in Labotan Kandi Village, Banggai Kepulauan Regency, Central Sulawesi. The number of stunted toddlers recorded based on the February 2022 weighing was 19 children. Data collection was carried out through a series of observations, interviews, and documentation studies. The findings show that there are several factors causing stunting under-fives as limited parental knowledge regarding stunting problems that many children/toddlers experience. In addition, there are several other contributing factors, namely low education (the majority do not go to school and only graduate from elementary school), are trapped by poverty and economic instability, high rates of early marriage, limited access to health services, and minimally implemented local food processing. by a stunting toddler mother in Labotan Kandi Village, Banggai Islands Regency. From these findings, it appears that the problem of stunting still needs to find solutions and appropriate management policies.